2010
DOI: 10.1016/j.epsl.2009.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Noachian–Hesperian geologic history of the Echus Chasma and Kasei Valles system on Mars: New data and interpretations

Abstract: New high-resolution datasets have prompted a mapping-based study of the 2500-km-long Echus Chasma and Kasei Valles system that utilizes geomorphic details, stratigraphic relations, and cratering statistics derived from the new datasets. Our results suggest that between the Hesperian and Amazonian Epochs on Mars (3.7 Ga to Recent) the study area was affected by at least 4 episodes of widespread volcanic activity and 4 periods of episodic fluvio-glacial activity. This paper discusses the Noachian to Hesperian (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…7A, B, 12B, 13A and B). Compared to Ast, smooth plains units have relatively few flow features, the exceptions being sinuous channels and aggradational streamlined features similar to those observed in Kasei Valles (Chapman et al, 2010) (Fig. 10D).…”
Section: Evidence Of Volcanic Activitymentioning
confidence: 55%
See 2 more Smart Citations
“…7A, B, 12B, 13A and B). Compared to Ast, smooth plains units have relatively few flow features, the exceptions being sinuous channels and aggradational streamlined features similar to those observed in Kasei Valles (Chapman et al, 2010) (Fig. 10D).…”
Section: Evidence Of Volcanic Activitymentioning
confidence: 55%
“…This intimate relationship between tectonic, volcanic, and aqueous activity augments current ideas about complexity of the Memnonia Fossae region and its relationship to Tharsis-related volcanism and tectonics. Ares Valles and the Kasei Valles and Echus Chasma system have been suggested to share this episodic behavior, but at a much earlier time in martian history (Warner et al, 2009;Chapman et al, 2010), indicating that Mangala Valles represents a younger expression of what may be a similar subsurface process. Detailed comparative studies of other more recently active fluvial-volcanic systems, such as Athabasca Valles (Jaeger et al, 2007(Jaeger et al, , 2010, may aid in determining the extent to which repeated fluvial and volcanic activity has extended into the Amazonian Period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the Echus Chasma and Kasei Valles system, Chapman et al (2010a) found closely interspersed episodes of volcanic and fluvio-glacial activity, with flood basalt emplacement in Kasei occurring at 3.7 Ga, the formation of Echus Chasma at 3.6 Ga with early flooding sourced from the west. A cycle lasting from 1.8-1.0 Ga began with fluvial erosion of a narrow channel in the Tharsis Montes formation in north Kasei Valles followed by episodic catastrophic floods sourced from Echus Chasma.…”
Section: Geologic Histories and Mappingmentioning
confidence: 99%
“…(1) The large areal extent of single HRSC nadir images (minimum width of 62.5 km at 12.5 m/pixel and variable lengths up to several 1000 km) are particularly favorable for mapping of volcanic deposits and edifices at scales of about 1:40,000 (e.g., Bleacher et al, 2007aBleacher et al, , 2007bChapman et al, 2010aChapman et al, , 2010bPlatz and Michael, 2011;Hauber, 2012, 2013). Colored views of the Martian surface based on the red, green, blue, and near-infrared channels also deliver additional information that assist in distinguishing surface domains, and when combined with OMEGA data in particular and provide information on the composition of volcanic materials.…”
Section: Endogenic Processesmentioning
confidence: 99%